Success of digitalization in the field of below the line marketing in Bangladesh. analyzing digital world project of Asiatic Exp Marketing Limited - Mahin, Jannatul Tamzida (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.